From 'Opening Up' to Democratic Renewal: Deepening Public Engagement in Legislative Committees. Issue 1 (7th August 2017) - Hendriks, Carolyn M.; Kay, Adrian
Abstract : Many legislatures around the world are undergoing a 'participatory makeover'. Parliaments are hosting open days and communicating the latest parliamentary updates via websites and social media. Public activities such as these may make parliaments more informative and accessible, but much more could be done to foster meaningful democratic renewal. In particular, participatory efforts ought to be engaging citizens in a central task of legislatures – to deliberate and make decisions on collective issues. In this article, the potential of parliamentary committees to bring the public closer to legislative deliberations is considered. Drawing on insights from the practice and theory of deliberative democracy, the article discusses why and how deeper and more inclusive forms of public engagement can strengthen the epistemic, representative and deliberative capacities of parliamentary committees. Practical examples are considered to illustrate the possibilities and challenges of broadening public involvement in committee work.